Jamaica’s Effort in Improving Universal Access within Fiscal Constraints - Chao, Shiyan (World Bank, Washington DC, 2013)
Jamaica's primary health care system was a model for the Caribbean region in the 1990s. Because of it, Jamaicans enjoy relatively better health status than people in other countries of similar income level in the Caribbean region. However, Jamaica's health system is being severely challenged by persistent and reemerging infectious diseases and by the rapid increase in noncommunicable diseases (NCDs) and injuries. At the same time, the country has suffered from low economic growth and carries a high debt burden, which leaves limited fiscal space for improving health care. The Government of Jamaica has been trying to sustain the gain in health outcomes and improve access to health care for its population in an environment of constrained resources during the last decade. With the establishment of the Jamaica National Health Fund (NHF) in 2003 and the abolition of user fees at public facilities in 2008, the Government of Jamaica has taken steps toward achieving universal coverage. This study reviews the achievements and challenges in expanding universal access in Jamaica and assesses the impact of the NHF's drug-subsidy programs and the abolition of user fees on universal access, and discusses policy options for achieving universal coverage.